Quantitative understanding of HepaRG cells during drug‐induced intrahepatic cholestasis through changes in bile canaliculi dynamics - Rie Sonoi; Yoshihisa Hagihara (Wiley, 2022)
Abstract An understanding of the quantitative relationship between bile canaliculus (BC) dynamics and the disruption of tight junctions (TJs) during drug‐induced intrahepatic cholestasis may lead to new strategies aimed at drug development and toxicity testing. To investigate the relationship between BC dynamics and TJ disruption, we retrospectively analyzed the extent of TJ disruption in response to changes in the dynamics of BCs cultured with entacapone (ENT). Three hours after adding ENT, the ZO‐1‐negative BC surface area ratio became significantly higher (4.1‐fold) than those of ZO‐1‐positive BCs. Based on these data, we calculated slopes of surface area changes, m, of each ZO‐1‐positive and ZO‐1‐negative BC. BCs with m ≤ 15 that fell within the 95% confidence interval of ZO‐1‐positive BCs were defined as ZO‐1‐positive. To validate this method, we compared the frequency of ZO‐1‐positive BCs, FZ, with that of BCs with m ≤ 15, FT, in culture using drugs that regulate TJ, or induce intrahepatic cholestasis. FT values were correlated with FZ under all culture conditions (R2 = .99). Our results indicate that the magnitude of BC surface area changes is a factor affecting TJ disruption, suggesting that maintaining TJ integrity by slowing BC dilation inhibits cell death.